Decentralizing Civic Learning: The Pedagogical Potential of the Civic Kolaborasik Community as a Third Space for University Students - Tity Kusrina; Ibnu Sulaiman; Zindan Baynal Hubi; Kireida Rona Islam; Hilman Gufron; Tity Kusrina; Ibnu Sulaiman; Zindan Baynal Hubi; Kireida Rona Islam; Hilman Gufron (Universitas Negeri Malang, 2026)
The background of this research is the conflict between the idealism of the Pancasila and Civic Education curriculum and the reality of economic pragmatism in industrial areas, which triggers student apathy and academic burnout due to rigid, one-way learning models. To analyze the role of the Civic Kolaborasik community as a